2023
DOI: 10.1080/02670836.2023.2187156
|View full text |Cite
|
Sign up to set email alerts
|

Si3N4–TiN conductive ceramic composites: topography on EDMed surfaces and precise drilled holes

Abstract: In this study, it is challenging to drill a 5 mm hole in a Si3N4–TiN conductive ceramic composite, specifically when attempting to identify an association between EDM machining inputs such as current, pulse on-time, pulse off-time, dielectric pressure and spark gap and performance parameters like as Material Removal Rate, Electrode Wear Rate, Average Surface Roughness, and geometrical tolerances such as Cylindricity, Circularity and perpendicularity. The study examines the surface deformations of a composite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The study reported the form (perpendicularity) tolerance index for Inconel 718 to be in the range of 50-55 (dimensionless, scaled by the machining time) and for Inconel 625, in the range of 15-20 (dimensionless, scaled by the machining time) for higher values of the peak current. Selvarajan et al [8] explored the effect of EDM drilling process parameters like the current, pulse on-time, pulse off-time, dielectric pressure, and spark gaps on performance parameters such as the material removal rate, electrode wear rate, and average surface roughness, and on geometrical tolerances such as the cylindricity, circularity and perpendicularity of drilled holes in Si3N4-TiN composites. The experimental results indicate that utilizing a copper electrode for machining can yield a favorable surface finish, accompanied by enhanced machining accuracy, tighter geometrical tolerances, and reduced irregularities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study reported the form (perpendicularity) tolerance index for Inconel 718 to be in the range of 50-55 (dimensionless, scaled by the machining time) and for Inconel 625, in the range of 15-20 (dimensionless, scaled by the machining time) for higher values of the peak current. Selvarajan et al [8] explored the effect of EDM drilling process parameters like the current, pulse on-time, pulse off-time, dielectric pressure, and spark gaps on performance parameters such as the material removal rate, electrode wear rate, and average surface roughness, and on geometrical tolerances such as the cylindricity, circularity and perpendicularity of drilled holes in Si3N4-TiN composites. The experimental results indicate that utilizing a copper electrode for machining can yield a favorable surface finish, accompanied by enhanced machining accuracy, tighter geometrical tolerances, and reduced irregularities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These reasons led us to perform experimental research, the goal of which was to achieve significant progress in optimizing the quality of the machined surface while maintaining high productivity of the electrical discharge process. At the same time, we would like to contribute to the database of already existing knowledge through clear formulations of particular laws in relation to the processes that take place directly on the machined surface during the electrical discharge [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the proposed neural network model enhanced with optimized machining parameters is effective in estimating the MRR. The extensive experimental research carried out, as described in the works of several authors [30][31][32][33][34], demonstrates that there is a wide range of input parameters for the electrical discharge process, which significantly affect the output qualitative parameters of machined surfaces in addition to the quantitative performance parameters of the process. Therefore, researchers [35][36][37][38][39][40][41][42], who solved the problem of multi-objective optimization of various Non-Traditional Machining processes (NTM) using an a priori approach, provided a different perspective on the issue.…”
Section: Introductionmentioning
confidence: 99%